Traditional and modified 5-0-5 change of direction test: normative and reliability analysis - Ryan, C.; Uthoff, A.; McKenzie, C.; Cronin, J. (Strength and Conditioning Journal, 2022)
Change of direction (COD) ability is an important performance factor in many field and court sports. A common COD maneuver is the 180-degree turn, which is commonly assessed through the 5-0-5 COD test. Coaches and practitioners need to assess an athlete's COD performance and have access to normative data for these assessments. This review focuses on the traditional and modified 5-0-5 COD test. The 5-0-5 COD performance results have been gathered across 50 different studies and 11 different sports to create sport, sex, and level specific normative data so performance comparisons can be made, which in turn can drive programming to better effect. The reliability of both the traditional and modified 5-0-5 COD tests has been evaluated and discussed. Traditional COD ability of male athletes is better understood given there were 300 male athletes, compared with 62 female athletes. On average, males were 6.03% faster than females. Elite males were 7.78% faster than subelite and novice males, and subelite females were 3.30% faster than novice female athletes. Further research or collation of normative data is needed on female, youth, and elite cohorts to build more comprehensive databases.